2014
DOI: 10.1002/ejoc.201403153
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium‐Salt‐Tagged IMesAuCl Complexes and Their Application in Gold‐Catalyzed Cycloisomerization Reactions in Water

Abstract: The total synthesis and characterization of ammonium‐salt‐tagged IMesAuCl complexes is described. Moreover, we have demonstrated their catalytic activity and recyclability in cycloisomerization reactions of allenic and acetylenic alcohols in water. The water‐soluble gold catalysts can be stabilized by the addition of LiCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…Generally, [AuCl] complexes are inactive in catalysis and dehalogenation is required to activate the complex, especially when using phosphines as a ligand. [51][52][53][54] Surprisingly, using the M 12 L 24 nanospheres, conversion of the substrate was seen at local concentrations of 0.27 M and higher. Moreover, it was observed that the activity of the catalyst increases with the local gold catalyst concentration.…”
Section: L 24 Cagesmentioning
confidence: 93%
“…Generally, [AuCl] complexes are inactive in catalysis and dehalogenation is required to activate the complex, especially when using phosphines as a ligand. [51][52][53][54] Surprisingly, using the M 12 L 24 nanospheres, conversion of the substrate was seen at local concentrations of 0.27 M and higher. Moreover, it was observed that the activity of the catalyst increases with the local gold catalyst concentration.…”
Section: L 24 Cagesmentioning
confidence: 93%
“…The next step was to examine the reactivity and recyclability of the new gold catalysts in transformations of unsaturated substrates in bulk water. As benchmark reactions, we selected the cycloisomerization of α‐hydroyallene 30 to 2,5‐dihydrofuran 31 , as well as, the intramolecular lactonization of pent‐4‐ynoic acid 32 to 33 (Scheme ) . Initially, we examined the cyclization of allene 30 in the presence of the 4 NHC‐gold(I) complexes obtained by nucleophilic substitution ( 6 , 9 a , 9 b , 9 c ) under standard conditions (5 mol% catalyst, water, room temperature, 24 h; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it appears that a slight leaching and/or decomposition of the catalyst by the acidic reaction medium is taking place . All other β‐CD‐tagged NHC‐gold(I) complexes also show excellent catalytic activity and recyclability in this lactonization, without formation of an alkyne hydration side product …”
Section: Resultsmentioning
confidence: 99%
“…9,10 Since the first synthesis of a sulfonated NHC-metal complex by Herrmann et al, the number of reports about water-soluble NHC ligands has been increasing steadily. 11 Moreover, we could successfully demonstrate their high stability and recyclability in water. 11,12 More often, an amino group of the final NHC-metal complex is quaternized with a Brønsted acid.…”
Section: Introductionmentioning
confidence: 91%
“…For this purpose, N-heterocyclic carbene (NHC) metal complexes were linked to water-soluble polymers 3,4 or silicabased surfaces 4 and carbohydrates. 11,12 More often, an amino group of the final NHC-metal complex is quaternized with a Brønsted acid. 9,10 Since the first synthesis of a sulfonated NHC-metal complex by Herrmann et al, the number of reports about water-soluble NHC ligands has been increasing steadily.…”
Section: Introductionmentioning
confidence: 99%